Excellent Supervision: The Residents' Perspective - Shanfield, Stephen B. (American Psychiatric Press, Inc, 2001)
Former residents rated their videotaped psychotherapy supervision sessions on how helpful their supervisors were as teachers during the session. Residents' and experts' ratings of the same videotape were compared and found to have no significant correlation. However, male residents were less critical than either female residents or experts. Former residents were also interviewed. Supervisors were rated as excellent when they were accepting and also when they provided guidance about highly charged clinical dilemmas. Discussion of the impact of the residents' personal experiences on the clinical encounter was also rated high and is best understood from an adult developmental perspective. The findings reveal the lasting value of sympathetic supervisors acknowledging personal concerns and are likely mirrored in all clinical settings.